Stone tool transport by wild Burmese long-tailed macaques (Macaca fascicularis aurea). (June 2016) - Haslam, Michael; Pascual-Garrido, Alejandra; Malaivijitnond, Suchinda; Gumert, Michael
Abstract: Archaeologists have used stone transport as a proxy to understand a variety of cognitive, logistical and social problems faced by human ancestors. In the same way, tool transport in our close relatives, non-human primates, has been seen as an important indicator of material selection proclivities, and as a contributing factor to the formation of activity sites as part of niche construction processes. Non-human primate transport behaviour also assists in framing evolutionary scenarios for the emergence of stone tool use in the hominin lineage. Here, we present the first study of directly observed stone tool transport in wild and unhabituated Burmese long-tailed macaques ( Macaca fascicularis aurea ) in Thailand. These macaques were observed during intertidal foraging activities, during which they pound open hard-shelled molluscs with stone tools. We recorded 2449 transport bouts, when a long-tailed macaque carried a stone tool from one prey target to the next, and found that on average the same tool was used to sequentially consume nine prey items in each foraging episode. The maximum number of prey items consumed in a single episode was 63. We found that tools used to open sessile oysters typically were used to consume more prey per episode than those employed on motile prey, and females transported tools further than males. Heavier tools (> 200 g) were rarely transported more than a few metres, but the longest transport distance was over 87 m. Importantly for primate archaeological analysis of macaque tool use sites, we found that the median transport distance was 0.5 m, meaning that tools are very often used in the immediate vicinity of the place they were collected by a macaque. Highlights: Wild macaques ( Macaca fascicularis aurea ) used stones to pound open intertidal prey. Stone tools were usually transported short distances (median 0.5 m, maximum 87 m). Tools were used on an average of nine prey items (maximum 63 items for one tool). Female macaques transport tools significantly further than males. Macaque tool transport creates recognisable, interpretable archaeological sites.